Vulnerability to electric shocks in the regionally−ischemic ventricles - Rodriguez, B; Tice, B; Blake, R; Gavaghan, D; Trayanova, N (2006)
Although the majority of patients undergoing defibrillation suffer from coronary heart disease, little is known about defibrillation in the setting of ischemic disease. The goal of this study is to aid understanding of defibrillation failure in ischemic hearts by studying changes in cardiac vulnerability to electric shocks the first 10 min following LAD occlusion. To d